Tecnologias acordes aplicadas al diseño como experiencias didácticas en instalaciones complementarias - Gallipoliti, Virginia A. (2019)
A teaching experience is presented in which the development of the practical work of the subject Facilities II of the professional career of Architecture and Urbanism of the National University of the Northeast allowed to observe the incorporation of materials, technologies and innovative procedures in front of traditional slogans imparted The lighting, Acoustics, Air Conditioning and Renewable Energy are raised as central issues in the complementary facilities of homes and buildings at height, and they incorporate the concepts of sustainability of the same, for which use of new technological materials is made acoustic panels and acoustic phonics, calculation of the thermal transmittances of paramentos chords to the bioclimatic region, use of solar equipment in the generation of hot water or electric power, use of green walls and green roofs, lamps of last generation and equipment of low consumption, etc. The degree of depth of the cases solved by the students is analyzed, the pertinence and the feasibility of putting it into practice, as well as the degree of commitment of the group with these new themes. We consider a renovating experience that will be improved with the contributions of the professors of the chair adapting the guides and slogans of the practical works.